Makna Pendidikan Anak Usia Dini Dalam Perjanjian Baru: Makna, Pendidikan Anak Usia Dini, Perjanjian Baru - Steven Tubagus (Institut Agama Kristen Negeri Kupang, 2022)
The background of the problem of knowledge crisis to parents in educating children so that mistakes occur in bad behavior towards children, for example shouting, slamming something when angry, hitting, littering, being lazy, or other bad attitudes. The Meaning of Early Childhood in the New Testament. The purpose of this paper is to describe the theological study of the meaning of early childhood education in the New Testament. By analyzing the text in accordance with the principles of exegesis, to get the meaning contained in the context of the meaning of early childhood education in the New Testament. The results of the descriptive analysis of the meaning of early childhood education in the Bible are first, children know the truth. Early childhood knows the truth, namely the word of God. Second, early childhood knows the Holy Spirit. Know the Holy Spirit as God and helper for early childhood to do the truth. Third, early childhood knows safety. Knowing salvation is knowing the sacrifice of the Lord Jesus on the cross, so that the faith of early childhood remains strong, and the heart of early childhood remains firm so that it makes children believe and believe that Jesus is the only way to heaven. The description of the meaning of early childhood education in the New Testament consists of: First. Knowing the Truth, knowing the truth about Christian values ??that must be instilled in early childhood, as early as possible from birth they are introduced to Bible teaching and knowledge of the Lord Jesus every day and continuously so that the word of God takes root and bears fruit in children . Second. know the Holy Spirit, early childhood must understand the role of the Holy Spirit as a helper in the lives of believers, so that early childhood can learn to listen to the voice of the Holy Spirit. Early childhood must also learn to follow the leading of the Holy Spirit in every action, so that children act honestly and righteously before God and others. The help of the Holy Spirit in the lives of early childhood will make the child aware of the function of the Holy Spirit as a helper. So that children will always come to God to ask for the help of the Holy Spirit. Third. Knowing Salvation, early childhood is taught to recognize the salvation carried out by Jesus who died on the cross to atone for the sins of all believers including the sins of early childhood, so that early childhood knows and understands that only through Jesus can get salvation. For the word of God in John 14:6 says I am the way, the truth and the life. No one comes to the Father, except through Me.